Towards an understanding of the dimensions and factors of management accounting change / Alhashmi Aboubaker Lasyoud and Nizar M. Alsharari. - Lasyoud, Alhashmi Aboubaker; M. Alsharari, Nizar (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2017)
This paper aims to discuss the main dimensions and factors of management accounting change and the current mainstream of research in the area by conducting a literature review in this subject. The paper uses the publicly available evidence to show that internal and external environment of organizations elite engaged in engendering the change in management accounting practices in developed and developing countries. The paper concludes that most previous studies have concentrated on management accounting change within large organizations. Researchers have been given little attention to the nature of change, in other words, the different types of change in management accounting and the processes that have taken place to affect it in Small and Medium-sized Enterprises (SME’s). It also concluded that there is no generally agreed upon definition of change in management accounting. In addition, little consideration has been given to the interrelations between causal factors of change.